Stereoscopic depth perception during binocular rivalry - Andrews, Tim (Frontiers in Human Neuroscience, 2011)
When we view nearby objects, we generate appreciably different retinal images in each eye. Despite this, the visual system can combine these different images to generate a unified view that is distinct from the perception generated from either eye alone (stereopsis). However, there are occasions when the images in the two eyes are too disparate to fuse. Instead, they alternate in perceptual dominance, with the image from one eye being completely excluded from awareness (binocular rivalry). It has been thought that binocular rivalry is the default outcome when binocular fusion is not possible. However, other studies have reported that stereopsis and binocular rivalry can coexist. The aim of this study was to address whether a monocular stimulus that is reported to be suppressed from awareness can continue to contribute to the perception of stereoscopic depth. Our results showed that stereoscopic depth perception was still evident when incompatible monocular images differing in spatial frequency, orientation, spatial phase or direction-of-motion engage in binocular rivalry. These results support the idea that binocular rivalry and stereopsis can coexist.